Project Management : Creating Sustainable Value - Clegg, Stewart R. (SAGE Publications, Ltd. (UK), 2024)
The second edition of this comprehensive textbook has been fully revised and updated, streamlining chapters and ensuring accessibility. Sustainability is now at the core of this textbook, showing students how projects can achieve success and create value for all stakeholders, ensuring projects for people, planet and prosperity.  Key features of this edition include:  • Sustainability Development Goal icons throughout highlighting where topics related to sustainability are covered.  • New and expanded coverage of agile approaches, remote working, digitalisation, artificial intelligence and Industry 4.0.  • Over 100 case studies from across different industries and countries such as Spain, Denmark, Qatar, Kenya, South Africa, Australia and Brazil.  With an array of pedagogical features and complemented by supplementary online resources, this textbook is essential reading for students and managers undertaking a project management course at either the undergraduate or postgraduate level.